Prediksi Waktu Tanam Kentang Sesuai Curah Hujan Menggunakan Analisis Spasial - Prayudi Lestantyo; Yuniar Setyo Marandy (-, 2022)
Experts have recently highlighted a decline in food production, especially potato production when combined with climate change. With fluctuations in rainfall, planting time greatly influences potato production. To stabilize it, we can adjust the potato planting time by analyzing climate changes and land changes. So that the use of technology for forecasting planting times that is suitable for potatoes can be done to create sustainable potato production. The study area for this research is Batu City. This is because Batu City is one of the productive potato producing areas. Data acquisition was carried out using secondary data from two government agencies, namely the Water Services Agency and the Meteorology, Climatology and Geophysics Agency. Table data obtained on monthly averages was processed using open source software, namely QGIS 2.14 (essen). Through research, we found a method to predict the appropriate potato planting time based on rainfall data. January to April is the recommended time to plant potatoes. Meanwhile, from June to October it is not recommended to plant potatoes.